STUDI PERBANDINGAN TINGKAT EFISIENSI BANK DOMESTIK DAN BANK ASING DI INDONESIA - Fredella Colline (Bina Ekonomi, 2010)
Global Crisis which occurred in 2008 will become a serious threat for banking industry in all over the world including Indonesia- Although nowadays banking performance is quite good, but there is tight competition between banks in lndonesia especially after foreign investors start to enter banking industry in lndonesia. A bank will be able to holdout in global crisis and face competition among banks, if it can operate efficiently. Efficient Bank can produce optimal output from a given set of input through its operation, so bank function as financial intermediary run well. According to Intermediary approach, a financial institution is viewed as mediator whereas bank borrow fund from Investors and lend it to customers. How important competition and efficiency issues makes the writer to do research about the comparison of efficiency level between Local and Foreign Bank in lndonesia. Efficiency is the ratio of output and input. This study use Descriptive Analysis Method with time-series and cross sectional study approach. Data is taken from Annual Financial Reports of fd banks for the period 2003 - 2007 which consists of I Local Banks and 8 Foreign Banks in lndonesia. The variables used are Credit, Interest Income, and Other Operational Income as output variables and Third parties fund, Interest Expense, Other Operational expense as input variables. This study use Data Envelopment Analysis (DEA) with DEAP2.1 to calculate the efficiency level for each bank. This study analyze how is the comparison of efficiency level between Local and Foreign Banks in lndonesia for period 2003-2007, and what factors to be increased by the banks which are inefficient. The result with DEA shows that Local Banks and Foreign Banks have operated quite efficiently, There are 3 local banks and 4 foreign banks which are efficient (efficiency level = 1 .0000)and the others have the efficiency level between 0.80 - 0.95. Local Banks is good at Credit and Interest Income Factors; meanwhile Foreign Banks is good at Other lncome Factor. The other factors are not quite different between Local and Foreign Banks.